Maternally expressed gene 3 regulates retinal neovascularization in retinopathy of prematurity - Yu Di (Wolters Kluwer Medknow Publications, 2022)
The mouse model of oxygen induced retinopathy is suitable for the study of various retinal neovascularization diseases, including retinopathy of prematurity. The maternally expressed gene 3 (MEG3) has been demonstrated to have an inhibitory effect on diabetic retinopathy. In this study, we investigated the role of MEG3 overexpression in oxygen-induced retinopathy in mice. The results showed that MEG3 overexpression effectively inhibited the production of retinal neovascularization in oxygen-induced retinopathy mice. It acts by down-regulating the expression of phosphoinositide 3-kinase, serine/threonine kinase, and vascular endothelial growth factor and pro-inflammatory factors. MEG3 overexpression lentivirus has a future as a new method for the clinical treatment of retinopathy of prematurity. The animal experiments were approved by the Animal Ethics Committee of Shengjing Hospital of China Medical University, China (approval No. 2016PS074K) on February 25, 2016.